Correlation Analysis of Social Status on Conservation Awareness in Sekaran, Semarang City - Fuedsi, Fajar Wahyushi; Humaira, Hanina (Universitas Muhammadiyah Yogyakarta, 2023)
This study, situated within the realm of humanities, education, law, and social sciences (HESS), explores the connection between social status and conservation awareness. It stems from the growing concern over global warming, as evidenced by the Earth's 0.89-degree Celsius temperature increase in 2022 compared to the 1951–1980 period. While global environmental challenges are well-documented, this study narrows its focus to explore the dynamics of conservation awareness within a specific community. The chosen locale for this research is Sekaran, a community within Gunungpati, Semarang City, closely connected with the University of Semarang (UNNES). The research combines qualitative methods with basic statistical analysis, employing questionnaires and interviews to collect data. Preliminary findings reveal that social status influences conservation awareness but in a nuanced manner. Contrary to expectations, high social status individuals don't consistently exhibit high conservation awareness, and conversely, those with lower social status aren't necessarily less conservation-conscious. These distinctions are observable in their daily behaviors. This study's novelty lies in its approach, delving into environmental issues from a social standpoint within a specific community. By concentrating on UNNES and the surrounding Sekaran community, it bridges the gap between global concerns and local perceptions and actions regarding environmental conservation. The results provide valuable insights into the intricate interplay between social status and conservation awareness, offering a deeper understanding of this vital topic.